Impact of Teamwork and Compensation on Employee Performance in Manufacturing Companies in Pasuruan, Indonesia - Mukhammad Zakkiy Badar; Dewi Komala Sari (Indonesian Journal of Law and Economics Review, 2019)
This study aims to determine the effect of job satisfaction, teamwork, and compensation on emplayee performance at PT. Wastra Karya Prima at Pandaan. This research is quantitative research with hypothesis testing. The sample used in this study were 100 employess at PT. Wastra Karya Prima at Pandaan. The analytical tool used is multiple linear regression analysis, coefficient of determination (R2), partial correlation coefficient, t test, F test and classic asumption test using SPSS version 18 for windows. This primary data was obtained from a questionnaire whose measurement used a Likert scale that tested the validity and reability and the data was declared valid and reliable.The results of this study prove that job satisfaction, teamwork, and compensation simultaneously influence emplayee performance. Job satisfaction. teamwork, and compensation have a partial effect on emplayee performance.